Analisis Penguasaan Konsep dan Kesulitan Siswa pada Materi Teori Kinetik Gas - Mimi Rohazal Yaumi; Sutopo Sutopo; Siti Zulaikah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: The purpose of this study was to analysed conceptual understanding and difficulties (misconceptions) of students in the kinetic theory of gases. Test consisted of 9 reasoned multiple choice questions administered after students study the material. From the results of the study, students get an average score of 7.1 from maximum score of 9. Students have mastered the concept of the relationship between ideal gas state quantities (pressure, volume, temperature) and kinetic energy of ideal gases. However, students still have difficulty in determining internal energy if the number of particles changing, the average speed of ideal gases, and the application of ideal gas law to the circulatory phenomena in the heart.Abstrak: Penelitian ini bertujuan untuk menganalisis penguasaan konsep dan kesulitan (miskonsepsi) siswa pada materi teori kinetik gas. Soal tes terdiri dari sembilan soal pilihan ganda beralasan yang diberikan setelah siswa mempelajari materi tersebut. Dari hasil penelitian, siswa mendapatkan skor rata-rata 7,1 dari skor maksimal 9. Siswa telah menguasai konsep hubungan antar besaran keadaan gas ideal (tekanan, volume, suhu) dan energi kinetic gas ideal. Namun, siswa masih mengalami kesulitan dalam menentukan energi internal dengan jumlah partikel gas yang berubah, kelajuan rata-rata gas ideal, dan aplikasi persamaan keadaan gas pada fenomena peredaran darah di jantung.